In situ experimental and modeling study on coal char combustion for coarse particle with effect of gasification in air (O2/N2) and O2/CO2 atmospheres. (1st December 2018) - Shen, Zhongjie; Zhang, Liqi; Liang, Qinfeng; Xu, Jianliang; Lin, Kuangfei; Liu, Haifeng
Highlights: Char combustion in the O2 /CO2 atmosphere was studied in the in situ experiment. Reaction front model was proposed and proved with agreements of experimental data. Surface char gasification absorbed heat, decreased temperature and combustion rate. Ratio of gasification to combustion was high at the beginning and then decreased. Abstract: This study applied the high temperature stage microscope to investigate coal char combustion in air (O2 /N2 ) and O2 /CO2 (volume, 21%/79%) atmospheres with the effect of gasification. A reaction front combustion model was also proposed, coupled with effect of char gasification, to predict the key parameters of char combustion in the O2 /CO2 atmospheres. The combustion process and particle evolution of coarse chars were observed and measured to calculate the carbon conversion. Experimental results showed that the burnout time of the char particle in the O2 /CO2 atmosphere in the was prolonged about 20–25%, compared to the burnout time of chars in air. The overall reaction rates of char particles in the O2 /CO2 atmosphere were lower than the rates in the air for different particle sizes. In addition, reaction rates from model prediction showed good agreements with the experimental data for different particle sizes both in the air and O2 /CO2 atmospheres, which proved the reaction front combustion model was applicable for the char combustion in this study. The reaction front combustion model also predicted that the reaction front decreased with burning time and mass consumption of char particle. For the char combustion in the O2 /CO2 atmosphere, the gasification with CO2 absorbed part of the combustion heat or radiation heat and caused lower particle temperatures and heat fluxes for different particle sizes. The proposed combustion model also predicted that although the effect of the gasification reaction was dominant at the beginning of combustion and then reduced, the conversion of particles was hindered compared to the combustion of char in air.